PENGARUH KUALITAS PELAYANAN, WORD OF MOUTH TERHADAP KEPUTUSAN PENGGUNAAN JASA NBTRANS TOUR AND TRAVEL - Alfi Rizka; Ugy Soebiantoro; Virginia Mandasari (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the extent to which Service Quality and Word of Mouth influence consumer decisions in using NBTrans Tour and Travel services in the Sidoarjo area. This research uses a quantitative approach. The sample selection was carried out through purposive sampling technique, with a population consisting of the Sidoarjo community and a total of 110 respondents. Data were collected through field observations, interviews, distributing questionnaires, and literature studies. Data analysis was carried out using the Structural Equation Modeling (SEM) method on a component basis through the Partial Least Square (PLS) approach. The results of the analysis show that Service Quality has a positive and significant effect on decisions in using services, as well as Word of Mouth which also has a positive and significant effect on consumer decisions on the selection of NBTrans Tour and Travel services.